How big is the little brain in the gut? Neuronal numbers in the enteric nervous system of mice, Guinea pig, and human. Issue 12 (5th August 2022) - Michel, Klaus; Kuch, Birgit; Dengler, Sophie; Demir, Ihsan Ekin; Zeller, Florian; Schemann, Michael
Abstract: Background: Despite numerous studies on the enteric nervous system (ENS), we lack fundamental knowledge on neuronal densities or total neuron numbers in different species. There are more anecdotal than actual figures on nerve counts. Methods: We used standardized preparation techniques and immunohistochemistry with validated panneuronal markers (human or mouse anti‐HuD/C) to determine neuronal densities in specimen from the entire gastrointestinal tract of mice, guinea pig, and humans. In parallel, we measured the dimensions of the gastrointestinal regions in mouse and guinea pig. For humans, we had to rely on literature data. Key Results: The average neuronal densities along the gastrointestinal tract were 35, 011 ± 25, 017 1/cm 2 for the myenteric and 16, 685 ± 9098 1/cm 2 for the submucous plexus in mice, 24, 315 ± 16, 627 and 11, 850 ± 6122 1/cm 2 for guinea pig myenteric and submucous plexus, respectively, and 21, 698 ± 9492 and 16, 367 ± 5655 1/cm 2 for human myenteric and submucous plexus, respectively. The total number of neurons in the ENS was 2.6 million for mice, 14.6 million for guinea pig, and 168 million for human. Conclusions & Inferences: This study reports the first comprehensive nerve cell count in mice, guinea pig, and human ENS. Neuronal densities were comparable between the three species and the differences in the total numbers of enteric neurons are likely due to body size and intestinal length. The number of enteric neurons is comparable to the number of neurons in the spinal cord for all three species. Abstract : We compared the number and density of enteric neurons in all parts of the gastrointestinal tract of mice, guinea pigs, and humans. Neuronal densities were comparable between the three species. Differences in the total numbers of enteric neurons are likely due to body size and intestinal length.